Potential Of Zakat, Infaq And Sedakah Funds In Msme Development In Lazismu, Medan City - Selamat Pohan; Nurrahmi Nurrahmi (Al-Sharf: Jurnal Ekonomi Islam, 2021)
Research that has been carried out at LAZISMU Medan City through the MSME Empowerment Program by providing assistance in the form of business capital and productive facilities using zakat, infaq and alms (ZIS) funds to MSME actors. With the MSME empowermwnt program, it is hoped that it can help increase mustahik’s business. The objectives of this study are: (1) to determine the potential of the ZIS funds from LAZISMU for the development of MSMEs; (2) knowing the ZIS fund distribution system carried out by LAZISMU Medan City; (3) as well as knowing the results of the distribution of ZIS funds to the development of MSMEs in Medan City. In this study using qualitative research methods with data collection starting from the results of interviews, observations and documentation. Based on the results of research that has been done, it can be seen that the potential of ZIS funds is very helpful for mustahik in developing their business. In the LAZISMU MSME empowerment program using two system, namely the offense system and the submission system which are expected to be able to improve the community’s economy, and for the results of the distribution of ZIS funds there are several MSMEs that have increased income, but there are also MSMEs that have decreased income.